PENEGAKAN HUKUM TERHADAP ORANG TUA YANG MELAKUKANPEMBUANGAN BAYI DI WILAYAH HUKUM KEPOLISIAN SEKTOR RETEH INDRAGIRI HILIR RIAU - Nurhasidah Nurhasidah; Emilda Firdaus; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Speech dumping is a crime that is increasingly prevalent, because it is a criminal offense fromthe influence of advances in science and technology that are not supported by the readiness of thecommunity to filter out any progress, consequently they are affected to do things that are not inaccordance with norms customs that apply to the community, so that the perpetrators can throw the babybecause they feel that the baby is not desirable, of course this needs to be addressed explicitly by thepolice as part of law enforcement that gives protection to the community to reveal the perpetrators ofcrime of the disposal of security and comfort for the community.In this thesis research the author uses sociological legal research. The location of the researchwas carried out in the legal area of the reteh sector. Data sources are supported by primary datasources, secondary. While data collection techniques are interviews and data studies using deductivemethods, namely analyzing general problems and then drawn to conclusions specifically based onexisting theories.From the results of the study it can be concluded that law enforcement for parents who disposeof babies in the legal area of the Reteh Sector Police is still not good because it is not processed inaccordance with applicable law by police officers in the jurisdiction of the Reteh Police Sector. Theinhibiting factor is the occurrence of criminal acts of baby disposal, namely internal factors and externalfactors that are interrelated in supporting the occurrence of criminal acts of baby disposal.Keywords: Law Enforcement - Disposal of infants – Reteh Indragiri Hilir – Riau